The influence of functional tooth units on body mass index in the elderly of the Jember Regency - Jevina Sicilia Ahliawan; Zahreni Hamzah; Mei Syafriadi (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2020)
Background: Tooth loss can disrupt the mastication process. Mastication disorders limit the amount of food a person consumes, affecting nutrition. The number of functional tooth units (FTUs) can affect nutritional status, measured using the body mass index (BMI). Purpose: The purpose of this study is to analyse the effect of the number of FTUs on the BMI in the elderly. Methods: This research was conducted in four villages in the Jember Regency. The number of subjects was 189, aged 45 years and over. The number of FTUs was calculated based on the anterior and posterior teeth that have contact with the antagonist and the BMI using the BMI formula. The data was analysed using a linear regression test; the level of significance is 0.005. Results: A simple linear regression test showed that there was significant correlation between FTU and BMI (p=0.366). Conclusion: The number of FTUs affects BMI; the higher the number of FTUs, the greater the BMI.